2014
DOI: 10.1371/journal.pone.0099598
|View full text |Cite
|
Sign up to set email alerts
|

Association of Branched-Chain Amino Acids with Carotid Intima-Media Thickness and Coronary Artery Disease Risk Factors

Abstract: BackgroundRecent studies have determined that branched-chain (BCAAs) and aromatic (AAAs) amino acids are strongly correlated with obesity and atherogenic dyslipidemia and are strong predictors of diabetes. However, it is not clear if these amino acids are capable of identifying subjects with coronary artery disease (CAD), particularly with subclinical atherosclerosis who are at risk of developing CAD.MethodsFour hundred and seventy two Chinese subjects (272 males and 200 females, 42–97 y of age) undergoing phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 22 publications
(36 reference statements)
1
60
2
3
Order By: Relevance
“…On the one hand, BCAA-rich diets or diets supplemented with BCAAs could improve metabolic health (14) and they could have benefits in patients with heart failure (15). On the other hand, several studies have shown detrimental associations between high plasma values of BCAAs and cardiometabolic diseases (16), especially obesity (17), insulin resistance (18), diabetes (7), and carotid intima-media thickness (19). Potential mechanisms underlying the effects of BCAAs are yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, BCAA-rich diets or diets supplemented with BCAAs could improve metabolic health (14) and they could have benefits in patients with heart failure (15). On the other hand, several studies have shown detrimental associations between high plasma values of BCAAs and cardiometabolic diseases (16), especially obesity (17), insulin resistance (18), diabetes (7), and carotid intima-media thickness (19). Potential mechanisms underlying the effects of BCAAs are yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…High serum branched-chain amino acid (BCAA; isoleucine, leucine, and valine) concentrations have been shown to be predictors or markers of insulin resistance (1), obesity (2, 3), diabetes (4, 5), and atherogenetic dyslipidemia (6, 7) and response to a test meal (8). A 12-year prospective follow-up study of initially normoglycemic individuals showed an association between high serum BCAA levels and incidence of type 2 diabetes (4).…”
Section: Introductionmentioning
confidence: 99%
“…Given these associations with IR, it is not surprising that a number of studies have shown higher BCAA levels in people with and prior to development of type 2 diabetes (T2D), although this has particularly been shown in Caucasian and Asian ethnic groups while not appearing to occur in African Americans . Similarly, higher BCAA levels track with cardiovascular disease …”
mentioning
confidence: 99%